Energy dissipation in reinforced concrete members before or after yielding. (27th January 2022) - Grammatikou, Sophia; Fardis, Michael N.; Biskinis, Dionysis
Abstract: Models for the pre‐ and post‐yield energy dissipation in reinforced concrete (RC) members are developed using a database of about 1200 tests with over 18, 000 load cycles. Before yielding, the equivalent viscous damping ratio exceeds 5%, especially if the member is initially uncracked. It can be considered by using either a dedicated pre‐yield hysteretic model with parameters established in the paper or global viscous damping and special provisions against double counting of energy dissipation. The post‐yield model can be combined with various post‐yield hysteretic laws. It accounts for the member's type, shear‐span‐to‐depth ratio and likely failure mode, the continuity, ratio, and surface characteristics of longitudinal bars, and for FRP wrapping, if any. Alternatively, it recognizes only four member types but accounts also for the transverse steel ratio and the normal stress due to the axial load.